Analysis of GFRP Composite I-Beam Subjected to Pulling Load (International Journal of Scientific Research and Management (IJSRM), 2014)
This paper presents a Finite Element Analysis of Adhesively bonded GFRP I-Beam in Pulling load which changes damage occurs, due to alterations in Adhesives used. The use of adhesive bonding in advanced composite structures has potential to reduce weight as compared to mechanical fasteners. Three tests were carried out for each composite I-beams with three Adhesives. The three adhesives used have different properties and they are used as per their data sheet and processing given by their respective companies. The result of the analysis work of these three beams are presented and next step of this work is experimental which will validate FEA result.